2000
DOI: 10.1021/cm000360l
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Plate-Form Manganese Oxide by Selective Lithium Extraction from Monoclinic Li2MnO3 under Hydrothermal Conditions

Abstract: Hydrothermal lithium extraction from well-crystallized Li 2 MnO 3 crystals was studied by scanning electron microscopy (SEM) observation, chemical, and X-ray diffraction analyses. Monoclinic Li 2 MnO 3 polyhedral crystals were prepared in an LiCl flux at 650 °C. The lithium extraction was carried out in a variety of H 2 SO 4 solutions with mole ratios of H + in the solution to Li + in the solid ([H + ] l /[Li + ] s ) of 0.1, 0.15, 0.25, 0.50, 0.75, and 1.0 under a hydrothermal condition at 140 °C. The lithium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
62
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 28 publications
10
62
0
Order By: Relevance
“…Since the oxidation of Mn 4+ to Mn 5+ in an octahedral oxygen environment is not common or accessible, one would expect Li 2 MnO 3 to be electrochemically inactive. However, this compound has been reported to show some electrochemical activity [18,19] due to the ion-exchange of Li + by H + as well as by the loss of oxygen from the lattice, similar to that observed on the acid leached Li 2 MnO 3 samples [20][21][22][23][24].…”
Section: Chemical Delithiation Of Layered LI 2 Mnosupporting
confidence: 64%
See 1 more Smart Citation
“…Since the oxidation of Mn 4+ to Mn 5+ in an octahedral oxygen environment is not common or accessible, one would expect Li 2 MnO 3 to be electrochemically inactive. However, this compound has been reported to show some electrochemical activity [18,19] due to the ion-exchange of Li + by H + as well as by the loss of oxygen from the lattice, similar to that observed on the acid leached Li 2 MnO 3 samples [20][21][22][23][24].…”
Section: Chemical Delithiation Of Layered LI 2 Mnosupporting
confidence: 64%
“…The authors reported that both the ionexchange of Li + by H + as well as loss of oxygen from the lattice takes place on deep charging. Also, chemical delithiation studies on Li 2 MnO 3 with aqueous acids have indicated that the delithiation proceeds both by an ion-exchange of Li + by H + as well as by an oxidation of oxide ions, involving an effective removal of Li 2 O from the lattice [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the considerable importance in many applications, such as batteries, electrochromic and magnetic materials, much attention has been paid to manganese oxides and oxyhydroxides [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been a number of investigation on the electrical, optical and electrochromic properties of the films [14][15][16], no systematic study appears to have been done on electrical and optical properties at varying deposition conditions. Moreover, there is a considerable lack of understanding [7,9,17], concerning the surface properties of the oxides in different applications oriented measuring techniques. Different microstructures caused by different deposition conditions could be the probable reasons for the lacks in understanding.…”
Section: Introductionmentioning
confidence: 99%